2021
DOI: 10.1093/hmg/ddab047
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 hyperactivation acts on piccolo to deplete synaptic vesicle stores in Huntington’s disease

Abstract: Synaptic dysfunction and cognitive decline in Huntington’s disease (HD) involve hyperactive A disintegrin and metalloproteinase domain-containing protein 10 (ADAM10). To identify the molecular mechanisms through which ADAM10 is associated with synaptic dysfunction in HD, we performed an immunoaffinity purification-mass spectrometry (IP-MS) study of endogenous ADAM10 in the brains of wild-type and HD mice. In the normal brain, proteins implicated in synapse organization, synaptic plasticity, and vesicle and org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…ADAM10 localizes presynaptically with SVs, suggesting a role in presynaptic regulation ( Lundgren et al, 2020 ). While Alzheimer disease (AD) is associated with reduced ADAM10 levels ( Kuhn et al, 2010 ), thereby resulting in excess amyloidogenic processing of amyloid precursor protein, ADAM10 is hyperactive in the HD brain at both pre- and postsynaptic localizations ( Cozzolino et al, 2021 ). Using immunoprecipitation followed by mass spectrometry and gene ontology analysis, it was found that the ADAM10 interactome exhibits substantial overlap with the wtHTT interactome; many of the shared interactors were identified as proteins essential for presynaptic function, thereby highlighting a putative functional role for both wtHTT and ADAM10 at the presynaptic active zone.…”
Section: Huntingtin and The Presynapsementioning
confidence: 99%
See 2 more Smart Citations
“…ADAM10 localizes presynaptically with SVs, suggesting a role in presynaptic regulation ( Lundgren et al, 2020 ). While Alzheimer disease (AD) is associated with reduced ADAM10 levels ( Kuhn et al, 2010 ), thereby resulting in excess amyloidogenic processing of amyloid precursor protein, ADAM10 is hyperactive in the HD brain at both pre- and postsynaptic localizations ( Cozzolino et al, 2021 ). Using immunoprecipitation followed by mass spectrometry and gene ontology analysis, it was found that the ADAM10 interactome exhibits substantial overlap with the wtHTT interactome; many of the shared interactors were identified as proteins essential for presynaptic function, thereby highlighting a putative functional role for both wtHTT and ADAM10 at the presynaptic active zone.…”
Section: Huntingtin and The Presynapsementioning
confidence: 99%
“…Using immunoprecipitation followed by mass spectrometry and gene ontology analysis, it was found that the ADAM10 interactome exhibits substantial overlap with the wtHTT interactome; many of the shared interactors were identified as proteins essential for presynaptic function, thereby highlighting a putative functional role for both wtHTT and ADAM10 at the presynaptic active zone. For example, both ADAM10 ( Cozzolino et al, 2021 ) and wtHTT ( Yao et al, 2014 ) bind to piccolo, a large cytomatrix protein that is critical for SV maintenance and efficient SV recycling ( Ackermann et al, 2019 ). Hyperactive ADAM10, which can be induced either by pathogenic polyQ expansion of HTT or by wtHTT loss ( Lo Sardo et al, 2012 ), disrupts the ADAM10/piccolo complex, resulting in depleted SVs at the readily releasable and reserve vesicle pools.…”
Section: Huntingtin and The Presynapsementioning
confidence: 99%
See 1 more Smart Citation
“…Each band of sample and control was subjected to an in situ trypsin hydrolysis procedure ( 24 ) and the peptide mixtures were analyzed by nano-Liquid Chromatography-tandem Mass Spectrometry (nano-LC-MS/MS) using an LTQ Orbitrap XL mass spectrometer (Thermo Fisher Scientific Inc., Waltham, MA, USA) equipped with a Proxeon nanoEasy II capillary High Performance Liquid Chromatography (HPLC). The nano-LC-MS/MS analyses were performed as described elsewhere ( 25 ). The raw data were processed into mgf files and proteins identified by means of Mascot licensed software (Matrix Science Boston, USA) using the Homo Sapiens National Center of Biotechnology Information (NCBI) database.…”
Section: Methodsmentioning
confidence: 99%
“…Another protein, huntingtin-interacting protein 1 (HIP1) is involved in cytoskeleton assembly and dendritic development [ 72 , 73 ], while binding of Htt to protein kinase C and postsynaptic density 95 (PSD95) regulates synaptic activity [ 74 ] and anchoring of postsynaptic glutamate receptors [ 75 ]. Through interaction with ADAM10 (A Disintegrin and metalloproteinase domain-containing protein 10), a transmembrane protease, Htt regulates presynaptic neurotransmission, an essential step for the normal functioning of synapses [ 76 , 77 ]. The protein has also an important role in the transcription of many genes.…”
Section: Normal and Mutant Huntingtinmentioning
confidence: 99%